2011
DOI: 10.1038/ng.934
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a susceptibility locus for thoracic aortic aneurysms and aortic dissections spanning FBN1 at 15q21.1

Abstract: Although thoracic aortic aneurysms and dissections (TAAD) can be inherited as a single-gene disorder, the genetic predisposition in the majority of affected people is poorly understood. In a multistage genome-wide association study (GWAS), we compared 765 individuals who had sporadic TAAD (STAAD) with 874 controls and identified common SNPs at a 15q21.1 locus that were associated with STAAD, with odds ratios of 1.6–1.8 that achieved genome-wide significance. We followed up 107 SNPs associated with STAAD with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
148
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 25 publications
(15 reference statements)
4
148
0
Order By: Relevance
“…Increased TGF-β1 signaling has been associated with defective fibrillin-1 in the pathology of MFS (2). Genome-wide association study identified FBN1 SNPs rs2118181 and rs10519177 to be associated with sporadic DPAA (4). The data were in part replicated by two independent studies (5,6), therefore strengthening intRODUCtiOn FBN1 mutations are associated with the development of dilative pathology of ascending aorta (DPAA) (1).…”
Section: Study Subjectssupporting
confidence: 66%
“…Increased TGF-β1 signaling has been associated with defective fibrillin-1 in the pathology of MFS (2). Genome-wide association study identified FBN1 SNPs rs2118181 and rs10519177 to be associated with sporadic DPAA (4). The data were in part replicated by two independent studies (5,6), therefore strengthening intRODUCtiOn FBN1 mutations are associated with the development of dilative pathology of ascending aorta (DPAA) (1).…”
Section: Study Subjectssupporting
confidence: 66%
“…Thus, it seems that common variation at the FBN1 locus may explain part of the susceptibility to aneurysm formation in STAAD. 134 Genome-wide copy number variant analysis in a large number of STAAD cases further suggested the involvement of VSMC adhesion and contraction in the development of TAA.…”
Section: Col4a1 Col4a3/4/5 Plod3)mentioning
confidence: 99%
“…Except for a genome-wide association study (GWAS), no previous studies have systematically investigated the genetic basis of sporadic spontaneous AD or the relationship between genotype and phenotype heterogeneity, especially for collagens and matrix metalloproteases (MMPs)/tissue inhibitors of MMPs (TIMPs) (LeMaire et al, 2011). However, GWASs were performed using only known genetic markers involved in both cases and healthy controls, the ability to identify novel pathogenesis is limited compared with direct sequencing (Marian and Belmont, 2011;Salomon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%